The e-waste management system in Poland - Marcin Cholewa; Joanna Kulczycka; Marzena Smol (Economic and Environmental Studies (E&ES), 2016)
The Waste Electronic and Electrical Equipment Regulations (WEEE) are intended to reduce the amount of e-waste being disposed of within the EU, and require EEE producers to pay for its reuse, recycling and recovery. It is estimated that 25% of the mass of WEEE produced in the EU-27 is collected and processed, and the remaining 75% is not recorded. In Poland a total of 1.5 kg/person was collected in 2008, and 4.4 kg/person in 2014, but it is not enough at the moment because in 2021 Poland will be obliged to recover 11 kg/person. The paper presents the barriers and challenges of the e-waste management system in Poland including an analysis of the legal, technological, ecological and market aspects, focusing on the recovery of non-energy raw materials. It was shown that the existing system of waste collection with Extended Producers Responsibility (EPR) based on EU regulations required some improvements to boost recovery and recycling of valuable materials and to be in line with the strategy for a circular economy. Despite the fact that there are over 1,500 companies involved in waste collection in Poland and waste is picked up for free from citizens, there are more and more activities promoting proper waste segregation, and waste collection is still the weakest link. The recycling companies are mainly SMEs that already implement the latest technologies and strategies for CSR and ISO 14001 certification and they are able to recover valuable resources. However, the variability of market conditions (low metal price) and regulations, as well as the dominance of the large Organisation of Electrical and Electronic Equipment Recovery (OEEER), results in competition with one another in order to obtain the lowest price, and as a result the recycling companies do not fully exploit their capacities. The consequence of these activities is the development of a grey zone. However, due to the increasing importance of materials recovery from waste and the fact that it is a priority in the most recent strategic documents in Poland, it should undergo dynamic development.
Keywords: O21; O32; O33; O37; O38; 330; Waste Electrical and Electronic Equipment (WEEE or e-waste); recycling; waste management system; WEEE management